2017
DOI: 10.5114/biolsport.2017.65995
|View full text |Cite
|
Sign up to set email alerts
|

Training-induced changes in physical performance can be achieved without body mass reduction after eight week of strength and injury prevention oriented programme in volleyball female players

Abstract: The purpose of the study was to analyse the changes in muscle strength, power, and somatic parameters in elite volleyball players after a specific pre-season training programme aimed at improving jumping and strength performance and injury prevention. Twelve junior female volleyball players participated in an 8-week training programme. Anthropometric characteristics, isokinetic peak torque (PT) single-joint knee flexion (H) and extension (Q) at 60º/s and 180º/s, counter movement jump (CMJ), squat jump (SJ), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
3
17
0
1
Order By: Relevance
“…However, our results differ from those published in previous work [14,20], which showed a positive impact of interval training on anaerobic markers (vertical jump and 10-m sprint). Other studies also reported improvements in lower limb power during countermovement jumps and squat jumps, which were not related to weight reduction [47]. The increase in power can be explained by the increased activity of the anaerobic glycolysis enzymes in skeletal muscles following interval training [48].…”
Section: Discussionmentioning
confidence: 93%
“…However, our results differ from those published in previous work [14,20], which showed a positive impact of interval training on anaerobic markers (vertical jump and 10-m sprint). Other studies also reported improvements in lower limb power during countermovement jumps and squat jumps, which were not related to weight reduction [47]. The increase in power can be explained by the increased activity of the anaerobic glycolysis enzymes in skeletal muscles following interval training [48].…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, we should acknowledge that volleyball is characterized by several ballistic efforts such as vertical jumps, shots, and rapid changes of direction. Thus, upper-body horizontal power and neuromuscular jumping performance might play an important role in team success and should be relevant for the physical preparation of the player (14).…”
Section: Introductionmentioning
confidence: 99%
“…Pass, set up, attack, block, etc., can be mentioned as examples of individual basic skills creating the game. All of them utilize various motor skills and abilities as jumps, swings or different ways of locomotion as well as power, agility, flexibility and speed of reaction ( Lehnert et al, 2017 ). Elite players are requested to possess a high level of the above mentioned skills and abilities; among them jumping ability that influences performance in some of volleyball’s basic skills.…”
Section: Introductionmentioning
confidence: 99%